Outcomes of "Early" Withdrawal of Corticosteroid Sparing Immunomodulatory Therapy for Birdshot Retinochoroidopathy. (3rd October 2019) - You, Caiyun; Meese, Halea; Stephenson, Andrew; Montieth, Alyssa; Ma, Lina; Hernandez, Mikhail; Kubaisi, Buraa; Syeda, Sarah; Foster, C. Stephen
ABSTRACT: Purpose : To review early withdrawal of immunomodulatory therapy (IMT) for birdshot retinochoroidopathy (BSRC). Design : Retrospective case-series of sixteen patients with Human-leukocyte-antigen-A29-positive BSRC treated with IMT ≥ 1 year and discontinued prior to achieving durable remission, observed ≥ 6 months off IMT. Results : Mean duration on IMT was 42.4 months. At discontinuation, quiescence was achieved in 75.0% of eyes. Subjects off IMT for 6 months, 1 year, and 3 years showed quiescence in 75.0%, 77.8%, and 80.0% of eyes. No significantly decreased vision was found 6 or 12 months after discontinuation. One eye experienced significantly decreased vision following 3 years without IMT. Significantly decreased amplitude on electroretinography and worse deviation parameters in perimetry were found in patients 3 years after withdrawal that experienced early discontinuation when compared with those achieving durable remission on IMT > 2 years (p < 0.05). Conclusion : The possibility of electroretinography and perimetry results worsening after early IMT discontinuation remained if the patients couldn't achieve remission.